Successful treatment with personalized dosage of imatinib in elderly patients with gastrointestinal stromal tumors. Issue 4 (April 2016) - Saponara, Maristella; Gatto, Lidia; Di Nunno, Vincenzo; Tabacchi, Elena; Fanti, Stefano; Di Scioscio, Valerio; Nannini, Margherita; Gruppioni, Elisa; Altimari, Annalisa; Fiorentino, Michelangelo; Santini, Donatella; Ceccarelli, Claudio; et al.
Abstract : Imatinib is the standard first-line therapy for metastatic gastrointestinal stromal tumors. It has markedly improved the prognosis and outcome of patients affected by gastrointestinal stromal tumors, especially in the case of exon 11 KIT mutations. Imatinib-associated adverse events are generally mild to moderate; however, in clinical practice, intolerance caused by chronic toxicities frequently leads to breaks in treatment. This is particularly true in elderly patients in whom age, decline in drug metabolism, and polypharmacy, with a possible drug–drug interaction, may influence the tolerability of imatinib. In the present article, we report our extensive experience with the management of imatinib therapy in a 'real' population, in particular in very elderly patients, discussing whether the use of personalized imatinib dosage could be a safe and advantageous option, enabling continuous administration, thus ensuring effective treatment. Only a few case reports in the literature provide data on outcome with low tailored dosage of imatinib and none of them has been carried out on a Western population. Here, we report four cases treated with low imatinib dosage as a safe and useful option enabling continued treatment with imatinib, improving tolerance, and maintaining good and lasting disease control.